PENGEMBANGAN PENILAIAN AUTENTIK MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Indah Khoirrul Mutakin (AS-SALAM, 2019)
This article aims to describe the development of authentic assessment of Islamic Religious Education subjects. Authentic assessment basically focuses on the balance between assessing the competence of attitudes, knowledge, and skills in accordance with the development of student characteristics. The type of research in this article uses qualitative research with field study methods. The results of this study indicate that the obstacles in carrying out authentic assessments lie in the very diverse characteristics of students that make it difficult for teachers to provide assessments, the limited time in conducting assessments related to student activity, there are several aspects that must be assessed thoroughly, and the instruments used are more than one. Teachers can follow up on these obstacles by planning and managing the learning process properly, participating in several training related to assessments based on the 2013 curriculum, seeking information and references related to authentic assessment, and developing self-creativity in order to find new ways to assess students. The positive contribution that is expected from this article is that authentic assessments can be developed in every educational institution to provide quality assessments and are not limited to the cognitive realm.